Penerapan Media Digital Papan Dakota sebagai Inovasi Pembelajaran Interaktif untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Lutfi, Lisa Ariani; Kusumastuti, Fitri Anisa (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
The low mathematics learning outcomes of elementary school students indicate the need for interactive, contextual, and enjoyable learning innovations. This study aims to implement and analyze the effectiveness of the Dakota Board digital media (mathematics dakon board) in improving elementary school students' mathematics learning outcomes on the Greatest Common Factor and Least Common Multiple material. The method used is Classroom Action Research with a collaborative approach implemented in several stages. The subjects of the study were fifth-grade students in an elementary school who actively participated in learning. Data collection techniques in this study included observing student engagement using observation sheets, measuring learning outcomes through tests (pretest and posttest), and filling out questionnaires to determine student learning motivation. The collected data were analyzed quantitatively using descriptive statistics and Paired Sample t-Test to measure the significance of differences in learning outcomes before and after treatment. The results showed that the use of the Dakota Board media can increase student engagement, strengthen motivation, and facilitate understanding of mathematical concepts. This media is also able to create an interactive and enjoyable learning atmosphere. The conclusion of this study is that the Dakota Board is effective as an innovative media to improve elementary school students' mathematics learning outcomes.Rendahnya hasil belajar matematika siswa sekolah dasar menunjukkan perlunya inovasi pembelajaran yang interaktif, kontekstual, dan menyenangkan. Penelitian ini bertujuan untuk menerapkan dan menganalisis efektivitas media digital Papan Dakota (papan dakon matematika) dalam meningkatkan hasil belajar matematika siswa SD pada materi Faktor Persekutuan Terbesar dan Kelipatan Persekutuan Terkecil. Metode yang digunakan adalah Penelitian Tindakan Kelas dengan pendekatan kolaboratif yang dilaksanakan dalam beberapa tahap. Subjek penelitian adalah siswa kelas V di salah satu sekolah dasar yang aktif mengikuti pembelajaran. Teknik pengumpulan data dalam penelitian ini meliputi observasi keterlibatan siswa menggunakan lembar observasi, pengukuran hasil belajar melalui tes (pretest dan posttest), serta pengisian angket untuk mengetahui motivasi belajar siswa. Data yang terkumpul dianalisis secara kuantitatif menggunakan statistik deskriptif dan uji Paired Sample t-Test untuk mengukur signifikansi perbedaan hasil belajar sebelum dan sesudah perlakuan. Hasil penelitian menunjukkan bahwa penggunaan media Papan Dakota dapat meningkatkan keterlibatan siswa, memperkuat motivasi, dan mempermudah pemahaman konsep matematika. Media ini juga mampu menciptakan suasana belajar yang interaktif dan menyenangkan. Simpulan dari penelitian ini adalah bahwa Papan Dakota efektif digunakan sebagai media inovatif untuk meningkatkan hasil belajar matematika siswa sekolah dasar.